2009
DOI: 10.1128/mcb.00544-08
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Peroxidase 3 Mediates the Antioxidant Effect of Peroxisome Proliferator-Activated Receptor γ in Human Skeletal Muscle Cells

Abstract: Oxidative stress plays an important role in the pathogenesis of insulin resistance and type 2 diabetes mellitus and in diabetic vascular complications. Thiazolidinediones (TZDs), a class of peroxisome proliferatoractivated receptor ␥ (PPAR␥) agonists, improve insulin sensitivity and are currently used for the treatment of type 2 diabetes mellitus. Here, we show that TZD prevents oxidative stress-induced insulin resistance in human skeletal muscle cells, as indicated by the increase in insulin-stimulated glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
129
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(137 citation statements)
references
References 57 publications
7
129
0
1
Order By: Relevance
“…GPx3 mediates the antioxidant effects of agonists of peroxisomeproliferator activated receptor (PPAR), a class of molecules that improves insulino sensibility in skeletal muscle and is used to treat type II diabetes. PPAR induced GPx3 expression by binding to peroxisome-proliferator response element (PPRE) in the GPx3 promoter (Chung et al, 2009). We believe that RA-mediated regulation of the GPx3 gene is indirect because the kinetics of GPx3 induction was slow, peaking at 48 hours.…”
Section: Discussionmentioning
confidence: 99%
“…GPx3 mediates the antioxidant effects of agonists of peroxisomeproliferator activated receptor (PPAR), a class of molecules that improves insulino sensibility in skeletal muscle and is used to treat type II diabetes. PPAR induced GPx3 expression by binding to peroxisome-proliferator response element (PPRE) in the GPx3 promoter (Chung et al, 2009). We believe that RA-mediated regulation of the GPx3 gene is indirect because the kinetics of GPx3 induction was slow, peaking at 48 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress has been implicated in the development of insulin resistance [24][25][26][27][28]; however the role of ROS in diabetic skeletal muscle is an emerging field. Recently, Chung et al demonstrated that treatment of human skeletal muscle cells with high levels of hydrogen peroxide led to destruction of the insulin signalling pathway, but that pretreatment with troglitazone could prevent this ROS-induced insulin resistance [29]. The production of ROS by skeletal muscle and the mechanisms by which this tissue mitigates oxidative damage in the context of type 2 diabetes are areas of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…Nrf2 activation is associated with down-regulation of NF-κB and iNOS (Mahmoud and Al Dera, 2015) and decreased production of pro-inflammatory cytokines (Mahmoud andAl Dera, 2015, Kamel et al, 2016;Mahmoud et al, 2017a,b,d,e). In addition, PPARγ activation modulates the expression of several antioxidant genes (Girnun et al, 2002, Chung et al, 2009 and induce anti-inflammatory responses (Yu et al, 2002).…”
Section: Discussionmentioning
confidence: 99%